The Use of Technology to Protect the Health of Athletes During Sporting Competitions in the Heat - Muniz-Pardos, Borja; Sutehall, Shaun; Angeloudis, Konstantinos; Shurlock, Jonathan; Pitsiladis, Yannis P. (Frontiers in Sports and Active Living, 2019)
During the 2019 IAAF World Championships in Athletics in Doha and the 2020 Olympic Games in Tokyo, minimum daily temperatures are expected to be in excess of 30 C. Due to the metabolic demands of the sporting events and the high environmental temperatures, the risk of exertional heat illness (EHI) is significantly higher. Careful planning is needed to ensure that athletes are protected from irreversible long-term health damage, or even death. The greatest benefit to exercise performance is gained after about 2 weeks of heat acclimation. For maximal adaptations to occur, the heat acclimation regime undertaken should closely mimic the environmental and intensity characteristics of the conditions expected during competition. Other acute strategies are available to enhance performance in the heat including the ingestion of cold (~4 C) beverages and the use of iced towels and ice garments; these acute strategies do not replace the need for heat acclimation. The importance of responding quickly to a hyperthermic athlete cannot be understated, as minimizing treatment time will greatly improve the chances of a full recovery. Treatment time can be minimized by notifying medical personnel about the athlete’s health status and the extent of any pre-competition heat acclimation strategy. Technology that allows the live transmission of physiological, performance, and biomechanical data to alert medical personnel of potential indicators of EHI should be considered. Prompt recognition of EHI will result in faster and more effective medical treatment which is crucial in protecting the athlete from irreversible and long-term health consequences, including death.